A microgrid cluster structure and its autonomous coordination control strategy. (September 2018) - Zhou, Xiaoping; Zhou, Leming; Chen, Yandong; Guerrero, Josep M.; Luo, An; Wu, Wenhua; Yang, Ling
Highlights: Microgrid cluster structure is proposed to coordinate power exchange among microgrids. Coordinated control method of PEU can realize mutual power support among microgrids. Coordinated control method of PEU can reduce the bus voltage and frequency deviation. Hierarchical coordinate control method of EP can stabilize the dc-link voltage. Hierarchical coordinate control method of EP can allocate net exchange power of PEU. Abstract: This paper proposes a microgrid cluster structure and its autonomous coordination control strategy. Unlike existing microgrids that are purely AC or DC, the microgrid cluster studied here is an interconnected system with multiple AC and DC microgrids, which enables mutual power support among microgrids and improves the utilization of renewable energy sources (RES). The proposed microgrid cluster structure is composed of power exchange unit (PEU), energy pool (EP), AC microgrids, and DC microgrids. PEU is used to coordinate power exchange among microgrids and EP. Meanwhile, the power coordinated control method combining the normalized droop-based control and adaptive control is proposed for PEU, which can effectively realize mutual power support among microgrids and reduce the bus voltage or frequency deviation in microgrids. In addition, the adaptive control strategy of PEU can ensure that the bigger the normalized index of microgrid is, the larger the active power exchange coefficient is, which can make all of microgrids operate around the rated state as much as possible. Besides, EP is mainly used to balance the system power, and the hierarchical coordinated control method of EP is proposed to stabilize the dc-link voltage and reasonably allocate the net exchange power of PEU. The proposed control strategy has been verified by the simulation and experimental results.